2022
DOI: 10.1136/bcr-2021-247495
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly enlarging pulmonary mass due to immune reconstitution inflammatory syndrome (IRIS) in an immunocompetent host with pulmonaryCryptococcus neoformans

Abstract: An immunocompetent man presented with Cryptococcus neoformans disease manifesting as a large pulmonary mass (cryptococcoma). Despite an initial induction course of 4 weeks of liposomal amphotericin B (LAmB), followed by 8 weeks of fluconazole, the cryptococcoma enlarged in size. Ten days into a second course of induction therapy with LAmB and flucytosine, the cryptococcoma markedly increased in size with encroachment on critical vascular structures. Due to concern for immune reconstitution inflammatory syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…The invasive infections by Cryptococcus neoformans or Cryptococcus gattii more frequently involve the lungs and the central nervous system (CNS) with a high mortality rate; besides, the muscles, skeletal, skin and soft tissues, abdominal viscera, eyes, and prostate of both previous healthy and immunosuppressed individuals may be affected. [1][2][3][4][5] More often, C. gattii causes mass lesions in CNS, while C. neoformans does it in lungs. 2 Risk factors include HIV/AIDS, solid organ transplant, immunomodulatory agents, liver cirrhosis, chronic renal disease, diabetes mellitus, malignancy, and autoimmune disease.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The invasive infections by Cryptococcus neoformans or Cryptococcus gattii more frequently involve the lungs and the central nervous system (CNS) with a high mortality rate; besides, the muscles, skeletal, skin and soft tissues, abdominal viscera, eyes, and prostate of both previous healthy and immunosuppressed individuals may be affected. [1][2][3][4][5] More often, C. gattii causes mass lesions in CNS, while C. neoformans does it in lungs. 2 Risk factors include HIV/AIDS, solid organ transplant, immunomodulatory agents, liver cirrhosis, chronic renal disease, diabetes mellitus, malignancy, and autoimmune disease.…”
Section: Dear Editormentioning
confidence: 99%
“…4 Tucker M et al also reported the development of IRIS in an immunocompetent male patient with rapidly enlarging cryptococcoma by C. neoformans that compressed vascular structures in spite of the four weeks of amphotericin B plus eight weeks of fluconazole. 5 The critical consequences of vascular encroachment were responsive to prednisone, and authors stressed that this was the first cryptococcal-IRIS in an immunocompetent host. 5 Finally, Brazilian authors described the findings of complete necropsy study of a 32-year-old man who died due to the acquired immunodeficiency syndrome (AIDS) and systemic mycobacteriosis, and presented with an unsuspected restrained prostatic cryptococcoma.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation